Budaya Komunikasi Keluarga di Perdesaan: Konteks Komunikasi Verbal dan Nonverbal - Ernita Arif; Rahmi Surya Dewi (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2022)
Communication determines a person's quality of life and success including in the family. Communication in the family can increase harmony in the family and quality of human resources. This study aims to analyze the communication culture of parents and children in rural areas. This research uses qualitative methods. The research was conducted in Agam Regency in June-September 2021, research informants were selected purposively or intentionally. Data were collected through in-depth interviews and observations. Data analysis was carried out using the Miles and Huberman technique. The results showed that the form of verbal communication that occurs in the family is in the form of using local language when calling children, telling children, advising children, telling stories with children, or chatting with children. Parents communicate with children according to the situation and conditions of the child. Parents still use harsh words to children. The use of non-verbal communication in the family in the form of facial expressions, body movements, voice intonation used differently by parents when calling children, telling children, advising children, telling stories with children and scolding children. Parents do not maximize non-verbal communication in terms of providing warmth to children such as hugging children, holding shoulders and giving appreciation or praise